Anti-Discrimination practices in social work: the animation approach - Максимовська, Н. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The article reviews animation approach to social work within the context of realization of anti-discrimination practices. It was proven that social work must provide traditional help to those who need it, as well as ensure self-assistance to reach a new quality level of social subjects’ interaction through productive pro-social activities. It was established that animation approach in social work field gains relevance in contemporary conditions as a mechanism of involving social subjects in building civic society and overcoming instances of discrimination by various traits. During realization of this approach, socio-educational influences of various fields of society’s life are activated, particularly anti-discrimination based on a certain trait in subjective filed of culture.